Ship Maneuvering in Bad Weather Conditions on MT. MPMT XII: Olah Gerak Kapal dalam Kondisi Cuaca Buruk di MT. MPMT XII - R., Sulastriani; Nurmala, Eka; Laju, I Kadek; Dahlan, Harris R.; Astria, Gusti (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2025)
Ships sailing or manoeuvring in the anchorage area, dock or jetty, or while sailing must meet the requirements and have permission from the local authority office where the ship will depart, with the issuance of a permit called a ship manoeuvring permit, the ship is considered seaworthy. An important aspect in a voyage that needs to be considered is the ship's manoeuvring ability caused by external factors such as sea waves, sea tides, weather factors causing external forces that will affect the ship's manoeuvring. This study uses a qualitative method that aims to explore the meaning, perception, and experience of individuals or groups in a particular context. The results of this study are: 1) Factors that affect ship manoeuvring include ship design and dimensions, propulsion system, rudder, cargo conditions, environmental conditions, ship speed, captain's expertise, supporting equipment; 2) Obstacles in ship manoeuvring during bad weather on the MT. MPMT XII ship include high waves and strong currents, strong winds, low visibility, decreased engine efficiency, reduced steering response, load factors, limited crew, damage to navigation and communication equipment; and 3) Ship maneuvering strategies during bad weather on the MT. MPMT XII ship include regulating ship speed, adjusting heading, optimizing engine and rudder usage, cargo management, actively monitoring environmental conditions, crew management, utilization of supporting equipment, adjusting shipping routes, maintaining communication with maritime authorities, and preparing for emergencies.